The Effect of Financial Ratios and Company Size on Stock Price (Empirical Study on Jakarta Islamic Index 70) - Sungkar, Hani Lutpiah; Budi Santoso, Suryo; Purwidianti, Wida; Hariyanto, Eko (International Journal of Management Science and Information Technology, 2025)
This study aims to find empirical evidence regarding the effect of several financial ratios, the population in this study are companies listed in the Jakarta Islamic Index 70 (JII70) index during the 2021-2023 period. The method used is quantitative with data analysis using multiple linear regression. The research sample was obtained from the IDX database and selected using the purposive sampling method with a total eligible sample of 43 companies for three years, resulting in 129 data. The results showed that Earning Per Share (X1), Return on Eqity (X2) and Price to Earnings Ratio (X4) had a positive and significant effect on stock price, Firm Size (X6) had a negative effect on stock price, but the variables Net Profit Margin (X3), Debt to Equity Ratio (X5) had no effect on Stock Price (Y).